Smart Growth - Johnson, Whitney (Ascent Audio, 2022)
Growth is the goal. To help people develop their potential, to articulate and become the self that they want to be, are capable of being, and that best serves them and others in the short and long term is what we as individuals and leaders strive toward. But how do we grow? It turns out it happens in a predictable way, which means we can understand where we are in our growth and chart a way forward. In this compact, complete guide, Whitney Johnson helps you envision how growth happens and proactively direct yourself, or others in your organization, to help make the leaps needed to achieve goals. The growth and learning journey comes in three phases, the Launch Point, the Sweet Spot, and the High End, and within each phase, we play roles that keep us moving toward our goals. Compelling examples of successful people will show you when growth is slow and why, and how to keep going, and what to do when growth and learning are almost too fast to keep up with, and how to leap from one growth journey to another. As individuals grow so do organizations and societies. Growth is learning put into action, ideally action that betters the world as we better ourselves and our small niches within it, both personal and professional. Growth occurs when learning is internalized, when we try something new and invest the effort to move it from being something we do, to something we are.
Online resource; Title from title page (viewed January 11, 2022)
Keywords: Audiobooks; Livres audio; Downloadable audio books